Mothers’ expectations of visiting services regarding newborns and nurselings - Schönbauerová, Andrea; Boledovičová, Mária (Journal of nursing, social studies and public health, 2018)
Objective: The research was focused on the issue of visiting services regarding newborns and nurselings, the mothers’ opinion sand expectations, their benefits and the reasons for refusing such form of care. Methods: The participants in the sample group were selected randomly. The group consisted of 254 mothers of toddlers between 12 and 24 months. The research method used a self-created semi-structured questionnaire. The gained data were processed using descriptive statistics. The chiquadrate test was used to establish the level of relation between the selected categorical data. The level of significance was set to α = 0.05. MS Excel was used for statistical processing. Results: We learned that 59.8% of mothers would welcome visiting services, and 40.2% would not be interested. This opinion was not influenced by the number of the respondents’ children, i.e. a statistical relation between the number of children and the mothers’ opinion on the necessity of visiting services was not proven. The mothers mainly expected the nurses to check their techniques of care and breastfeeding andhelp them to solve possible problems. The nurse was also expected to provide important information on childcare. The possible causes of the respondents’ lack of interest were stress over tidying up, disruption of privacy andthe feeling that they were being checked. 44.5% of mothers thought that the ideal frequency of nurse visits was only in the case of the first examination of the child after being discharged from hospital, and 29.5% thought that visits were only acceptable once a week during puerperium. Conclusion: The visiting service for a household with a newborn has its purpose and it should be offered to mothers. The paediatric nurses’ active participation in community activities shows their important role in the support of children’s health.
Keywords: průzkumy a dotazníky; Surveys and Questionnaires; Home Health Nursing; porodní asistentky; Postpartum Period; Maternal-Child Nursing; Nurse Midwives; domácí ošetřovatelství; ošetřovatelství v péči o matku a dítě; poporodní období